ENVIRONMENTAL EDUCATION IN SCHOOLS: TRANSFORMING AWARENESS AND PRACTICES FOR SUSTAINABILITY (REMUNOM, 2026)
Environmental education is one of the fundamental pillars for forming conscious, ethical, and engaged citizens regarding contemporary climate challenges. This study, designed as a theoretical essay based on an integrative literature review, analyzes innovative methodologies applied in schools to transform daily practices and build a robust culture of sustainability. The central objective is to investigate the effectiveness of Decision Engineering in designing interdisciplinary curricula that couple data intelligence with community participation. The methodology followed the six-stage protocol for integrative reviews, ensuring the rigor and traceability of the findings. The study highlights that integrating monitoring technologies and participatory governance acts as a lever for pedagogical value, mitigating the "technical debt" of discontinued environmental projects. It is concluded that the competitive advantage of educational institutions lies in the ability to transform socio-environmental information into practical and sustainable decisions, promoting regenerative education.